Long term follow up of biomarkers of podocyte damage and renal function in patients with and without preeclampsia - de Franco, Ylbe Palacios (J Bras Nefrol, 2018)
INTRODUCTION: preeclampsia can be associated with future renal disease. OBJECTIVES: To measure changes in renal function overtime in patients with preeclampsia. METHODS: urine and serum samples from eleven patients with preeclampsia and eight patients with a normal pregnancy were obtained during pregnancy, postpartum, and 3 years after delivery. Urine podocalyxin, protein, and serum creatinine were measured. RESULTS: after 3 years, there were no significant differences in urinary podocalyxin in patients with or without preeclampsia: 4.34 ng/mg [2.69, 8.99] vs. 7.66 ng/mg [2.35, 13], p = 0.77. The same applied to urinary protein excretion: 81.5 mg/g [60.6, 105.5] vs. 43.2 mg/g [20.9, 139.3] p = 0.23. Serum creatinine was 0.86 mg/dL [0.7, 0.9] vs. 0.8 mg/dL [0.68, 1] p = 0.74 in those with and without preeclampsia. In normal patients, urinary podocalyxin decreased from 54.4 ng/mg [34.2, 76.9] during pregnancy to 7.66 ng/mg [2.35, 13] three years after pregnancy, p = 0.01. Proteinuria decreased from 123.5 mg/g [65.9, 194.8] to 43.2 mg/g [20.9, 139.3], p = 0.12. In preeclampsia patients, urinary podocalyxin decreased from 97.5 ng/mg [64.9, 318.4] during pregnancy to 37.1 ng/mg within one week post-partum [21.3, 100.4] p = 0.05 and 4.34 ng/mg [2.69, 8.99] three years after, p = 0.003. Proteinuria was 757.2 mg/g [268.4, 5031.7] during pregnancy vs. 757.2 mg/g [288.2, 2917] postpartum, p = 0.09 vs. 81.5 mg/g [60.6, 105.5] three years later, p = 0.01. Two patients still had proteinuria after 3 years. CONCLUSIONS: in preeclampsia patients, postpartum urinary podocalyxin decreased before proteinuria. After three years, serum creatinine, urinary podocalyxin, and protein tended to normalize, although some patients still had proteinuria.